Human metapneumovirus in hospitalized children less than 5 years of age in Pakistan. Issue 6 (12th March 2018) - Yousafzai, Mohammad T.; Ibrahim, Romesa; Thobani, Rozina; Aziz, Fatima; Ali, Asad
Abstract : Acute respiratory infection (ARI) is the second leading cause of death in children less than 5 years of age worldwide. Human Metapneumovirus (hMPV) is associated with around 5‐7% of the total pneumonia admissions in children. The aim of this study was to determine the magnitude of hMPV associated hospitalizations among children, in Karachi, Pakistan. A 3 years prospective study was conducted at the Aga Khan University Hospital (AKUH), from August 2009 to June 2012. Children less than 5 years of age, admitted with ARIs, were enrolled. Throat swabs were collected and tested for hMPV using real‐time PCR. Multivariable log binomial regression analysis was performed. Out of 1150 children enrolled, hMPV was detected among 84/1150 (7%). About 87% of the enrolled children presented with cough, followed by fever (73%), nasal congestion (69%) and shortness of breath (68%). Of the hMPV positive subjects, most (56/84, 67%) were less than 12 months of age. The most common diagnosis in hMPV positive infants was pneumonia, followed by asthma and bronchiolitis. HMPV was identified year round, with peaks during February and August. Sore throat was found to be significantly associated with the hMPV infection (Adjusted RR 2.23; 95%CI 1.42‐3.52). The proportion of hMPV was higher among hospitalized infants with ARI. Pneumonia was the primary discharge diagnoses of patients who tested positive for hMPV. hMPV could be a target for future vaccine to further decrease the burden of ARI morbidity and possibly mortality in developing countries.